Laser Sensor with Fiber Optic Bragg Gratings for Measuring Physical Parameters - Vázquez, R.; García, C.; May, M.; Méndez, F.; Camas, J. (Revista Cubana de Física, 2010)
We present the operation of a fiber laser sensor made by an Er-bium Doped Fiber pumped at 980nm, an 4.23 km passive fiber and two fiber Bragg gratings placed at the ends of the laser cavity. Under normal conditions, the Bragg gratings have different reflection wavelengths and laser emission is not generated. The two Bragg gratings can be placed at the same reflection wavelength when the grating with the lowest reflective wavelength increases their temperature which can be used as a sensor element. The laser generation thus shows that the Bragg grating is increasing their temperature. We used a Peltier cell in order to gradually change the temperature.